Community Development Evaluation for MAMI SERA (Mangunharjo Mandiri Sejahtera) Program Initiated by PT. Pertamina Patra Niaga Aviation Fuel Terminal of Ahmad Yani - Hayfa, Hanna Hanifah; Amri, Shoiful; Winastu, Hadna Trie (Global Writing Academica Researching & Publishing, 2024)
Corporate Social Responsibility (CSR) is an effort undertaken by companies that involves the roles of entrepreneurs, government, and society to demonstrate social responsibility as one form of ethical embodiment in building long-term performance. The CSR initiative of PT Pertamina Patra Niaga Aviation Fuel Terminal of Ahmad Yani has implemented a community empowerment program, one of which is through the MAMI SERA (Mangunharjo Mandiri Sejahtera) program. This study aimed to evaluate the community empowerment program conducted by PT Pertamina Patra Niaga Aviation Fuel Terminal of Ahmad Yani through the MAMI program. The method employed in this study was descriptive qualitative. Data collection techniques included field observations, interviews, and documentation. The results show that the evaluation of the community empowerment program through the MAMI SERA program by PT Pertamina Patra Niaga Aviation Fuel Terminal of Ahmad Yani has successfully improved community welfare through the mentoring and development of the Trengginas Jaya Abadi Cooperative. However, ongoing evaluation is needed throughout the program to identify and address deficiencies. The evaluation also found that the MAMI SERA program requires a production house to market MSME products.